FgMet3 and FgMet14 related to cysteine and methionine biosynthesis regulate vegetative growth, sexual reproduction, pathogenicity, and sensitivity to fungicides in Fusarium graminearum - Zhao, Feifei; Yuan, Zhili; Wen, Weidong; Huang, Zhongyu; Mao, Xuewei; Zhou, Mingguo; Hou, Yiping (Frontiers in Plant Science, 2022)
Fusarium graminearum is a destructive filamentous fungus, which widely exists in wheat and other cereal crops. Cysteine and Methionine are unique sulfur-containing amino acids that play an essential role in protein synthesis and cell life, but their functions and regulation in F. graminearum remain largely unknown. Here we identified two proteins, FgMet3 and FgMet14 in F. graminearum, which are related to the synthesis of cysteine and methionine. We found FgMet3 and FgMet14 were localized to the cytoplasm and there was an interaction between them. FgMet3 or FgMet14 deletion mutants (ΔFgMet3 and ΔFgMet14) were deficient in vegetative growth, pigment formation, sexual development, penetrability and pathogenicity. With exogenous addition of cysteine and methionine, the vegetative growth and penetrability could be completely restored in ΔFgMet3 and ΔFgMet14, while sexual reproduction could be fully restored in ΔFgMet3 and partially restored in ΔFgMet14. ΔFgMet3 and ΔFgMet14 exhibited decreased sensitivity to Congo red stress and increased sensitivity to SDS, NaCl, KCl, Sorbitol, Menadione, and Zn ion stresses. Moreover, FgMet3 and FgMet14 nonspecifically regulate the sensitivity of F. graminearum to fungicides. In conclusion, FgMet3 and FgMet14 interacted to jointly regulate the development, pathogenicity, pigment formation, sensitivity to fungicides and stress factors in F. graminearum.